2010
DOI: 10.1364/ol.35.002840
|View full text |Cite
|
Sign up to set email alerts
|

Spatial-domain low-coherence quantitative phase microscopy for cancer diagnosis

Abstract: A microscopy technique, spatial-domain low-coherence quantitative phase microscopy (SL-QPM) is proposed for speckle-free, quantitative phase imaging of subcellular structures with subnanometer sensitivity. We quantified, for the first time to our knowledge, the refractive index of the cell nuclei on original unmodified histology specimens. We demonstrate that the refractive index of cell nucleus is highly sensitive in detecting cancer, especially in histologically normal-appearing cells from cancer patients. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
59
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(59 citation statements)
references
References 7 publications
0
59
0
Order By: Relevance
“…SL-QPM takes advantage of the ultrahigh sensitivity of the light interference effect to achieve nanoscale sensitivity not attainable with a conventional microscope. 4,5 Compared with other biomarkers, the nano-morphology marker has a few major advantages. First, it can be extracted from the clinical tissue histology specimens (glass-slide-based) prepared according to standard routine clinical protocols without any additional processing, thus easily can be integrated with the existing workflow of current pathology laboratories.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…SL-QPM takes advantage of the ultrahigh sensitivity of the light interference effect to achieve nanoscale sensitivity not attainable with a conventional microscope. 4,5 Compared with other biomarkers, the nano-morphology marker has a few major advantages. First, it can be extracted from the clinical tissue histology specimens (glass-slide-based) prepared according to standard routine clinical protocols without any additional processing, thus easily can be integrated with the existing workflow of current pathology laboratories.…”
Section: Discussionmentioning
confidence: 99%
“…1 The recent development in optical techniques has allowed the detection of these nanoscale structural properties. [1][2][3][4][5][6][7][8][9] These changes occur at a scale of about 20 to 1000 times smaller than what conventional optical microscope can detect. For example, partial-wave spectroscopy has shown that changes in the nano-structural properties could be highly sensitive for the detection of molecular alterations associated with carcinogenesis prior to the occurrence of phenotype.…”
Section: Introductionmentioning
confidence: 86%
See 3 more Smart Citations